ANÁLISE DO PROCESSO DE IMPLANTAÇÃO DO BALANCED SCORECARD (BSC) EM UMA INSTITUIÇÃO DE ENSINO SUPERIOR - Josilene Martins Rocha; Alam de Oliveira Casartelli (Revista Gestão Universitária na América Latina, 2014)
This study aims to evaluate the critical factors for the implementation of the methodology of Balanced Scorecard (BSC) in a higher education institution. The method used consisted of an exploratory research through in - depth interviews with eight managers who played an important role in the process of implementing the BSC. Data analysis began with transcription of the interviews and subsequent review of the content, being highlighted as positives the recognition of the i mportance of strategic planning for a higher education institution; the existence of a common strategic direction; the definition of comprehensive institutional priorities; the creation of a deployment team able to spread the BSC methodology; owning an in formation technology tool to support the process and rely the active participation of senior management. Moreover, the integration of the BSC system to others used by the University and the deepening of the long - term strategic management culture, were iden tified as challenges to greater ownership by the users of the tool.